PSYCHOGERONTOLOGICAL SUPPORT FOR DEMENTIATED ELDERLY PEOPLE - Leuck, Patrícia (Health and Society, 2024)
Psychopegerontological work has as its main objective the search for autonomy and independence for the elderly, helping to understand and accept the emotions and thoughts generated by the difficulties existing in the problems encountered at this stage of life. Understanding the concept of old age, aging, the brain aging process, and its pathologies are the key pieces for beginning good prevention and intervention work with the elderly. Stimulating their cognitive abilities in a preventive and interventional way is the focus of this study and the way in which psychopedagogy adds and contributes to multidisciplinary work and well-being based on autonomy and independence of the elderly and their families.